The Fall of Eve and the Fate of Her Daughters: Competing Interpretations of Genesis 3:13 in 1 Timothy and Gregory of Nazianzus - Klem, Matthew J. (Harvard theological review, 2025)
In 1 Timothy 2, the author claims that Eve alone was deceived, and not Adam, yet women can be saved through childbirth. In Or. 37, Gregory of Nazianzus construes Genesis 3 differently, insisting that both Eve and Adam were deceived and that both will be saved in the same manner. This article considers whether Gregory performs a subtly transgressive rewriting of 1 Timothy. To corroborate that Gregory is engaging 1 Timothy, rather than disregarding it, the article surveys early Christian reception of 1 Tim 2:14 through the lens of Elizabeth A. Clark’s categories of ascetic reading, and it explores how women function in Gregory’s corpus and how his own interpretive principles could render a transgressive rewriting intelligible. It concludes that Gregory may be transgressing 1 Timothy after the pattern of Jesus transgressing the Mosaic law on divorce, a spiritual transgression.